2007
DOI: 10.1095/biolreprod.107.060152
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Signaling in Mouse Oocytes1

Abstract: Continuous exposure of follicles/oocytes to elevated levels of insulin compromises embryonic developmental competence, although the underlying cellular mechanisms are unknown. The objectives of the present study were to determine whether mouse oocytes have insulin receptors and a functional insulin signaling cascade, and whether insulin exposure during oocyte growth or maturation influences meiotic progression and chromatin remodeling. Immunoblot and immunocytochemical analyses of germinal vesicle-intact (GVI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 59 publications
2
52
1
2
Order By: Relevance
“…However, 19 h insulin treatment of denuded oocytes did not alter phosphorylation of GSK3A or B. The effect of insulin treatment on other enzymes in the insulin signaling pathway in oocytes or cumulus cells is unknown [102]. The IGF-1 knockout mice have decreased granulosa cell proliferation and decreased GLUT1 [89,104], similar to results observed in blastocysts following PI3K inhibition [98].…”
Section: Insulinmentioning
confidence: 61%
See 2 more Smart Citations
“…However, 19 h insulin treatment of denuded oocytes did not alter phosphorylation of GSK3A or B. The effect of insulin treatment on other enzymes in the insulin signaling pathway in oocytes or cumulus cells is unknown [102]. The IGF-1 knockout mice have decreased granulosa cell proliferation and decreased GLUT1 [89,104], similar to results observed in blastocysts following PI3K inhibition [98].…”
Section: Insulinmentioning
confidence: 61%
“…Other studies in COCs showed that inhibition of the PI3K pathway reduced glucose uptake in response to FSH, but did not investigate the role of insulin [86]. The terminal enzyme in insulin signaling, glycogen synthase kinase 3A/B (GSK3A/B) is present in denuded oocytes [102]. However, 19 h insulin treatment of denuded oocytes did not alter phosphorylation of GSK3A or B.…”
Section: Insulinmentioning
confidence: 98%
See 1 more Smart Citation
“…The involvement of different MAPKs in oocyte meiotic progression was reported also in mice, where levels of MAPK14, MAPK3/MAPK1 and JNK kinases' activities were shown to vary with the stage of oocyte maturation (Baatout et al 2007). Members of insulin signalling cascade, including AKT and GSK3 were shown to play important roles in mice oocyte meiosis completion (Acevedo et al 2007a). In addition, GSK3 was reported as the only kinase capable to phosphorylate Aurora-A in Xenopus oocytes (Sarkissian et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, insulin signaling affects oocyte maturation and fertilization. 1,2 Mutations in the insulin signaling pathway in C. elegans can lengthen life span but reduce fertility. 3,4 Improper insulin signaling in Drosophila leads to reduced body size and female sterility.…”
mentioning
confidence: 99%